The Cantabrian Magdalenian : lateglacial chronology in Northern Iberian Peninsula - Álvarez Alonso, David (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The aim of this paper is to provide a chronologic summary of the Magdalenian period in the Cantabrian region. The article includes data resulting from the latest C14 and AMS tests and is conceived as a tool that might be useful to all investigators of this field. In addition, we propose a structured chronologic subdivision for this period which will take into account investigations using paleoclimatic, cultural and chronologic data.